Modifikasi Metode Setengah Reaksi untuk Menyetarakan Reaksi pada Pembelajaran Konsep Reaksi Redoks dan Elektrokimia di SMA - Sukisman Purtadi (Jurnal Cakrawala Pendidikan, 2006)
Redox reaction is one of difficult concept to be understood. It is coused mainly by existing reaction redox balancing methods that give students some difficultness. For that case, this paper was meant to discuss about modifying reaction redox balancing method so that it can be acquired more easily.Algebra mothod is too mathematical. The more complex the reaction is, the more diffcult its solution is. The complexity of rule of half reaction method on balancing redox reaction brings difficult under-standing on studens also. Even, on a particuler condition, balanceing process lead to break the rules.Half rection method modification can simplity the rule students have to rote. Simplifying the method will reduce student bourdon.. By this modification method, students neet just to remember that in every conditon. OH and H ion is used to balance O and H atom respectively.